Micromechanical model to predict the effect of temperature on the behavior of unsaturated porous media - Tran, Bao Viet; Chateau, Xavier (Vietnam Journal of Mechanics, 2023)
The homogenization method is used to investigate temperature effects on the water content-capillary pressure relationship and on the poro-mechanical behavior of unsaturated porous media. Two different phenomena have been considered: the temperature variations of surface tensions and the thermal dilatation of the solid phase in the framework of micromechanical models that are proposed in order to highlight the influence of the deformability of the solid phase on the macroscopic behavior. The result show that taking into account the coupling between the deformation of the porous space and the capillary effects can radically modify the prediction of the temperature influence on the capillary curve.